Immobilization of Superoxide Dismutase on Polyelectrolyte‐Functionalized Titania Nanosheets. (18th December 2017) - Rouster, Paul; Pavlovic, Marko; Szilagyi, Istvan
Abstract: The superoxide dismutase (SOD) enzyme was successfully immobilized on titania nanosheets (TNS) functionalized with the poly(diallyldimethylammonium chloride) (PDADMAC) polyelectrolyte. The TNS–PDADMAC solid support was prepared by hydrothermal synthesis followed by self‐assembled polyelectrolyte layer formation. It was found that SOD strongly adsorbed onto oppositely charged TNS–PDADMAC through electrostatic and hydrophobic interactions. The TNS–PDADMAC–SOD material was characterized by light scattering and microscopy techniques. Colloidal stability studies revealed that the obtained nanocomposites possessed good resistance against salt‐induced aggregation in aqueous suspensions. The enzyme kept its functional integrity upon immobilization; therefore, TNS–PDADMAC–SOD showed excellent superoxide radical anion scavenging activity. The developed system is a promising candidate for applications in which suspensions of antioxidant activity are required in the manufacturing processes. Abstract : New SOD : Superoxide dismutase (SOD) is successfully immobilized on titania nanosheets (TNS) functionalized with the poly(diallyldimethylammonium chloride) (PDADMAC) polyelectrolyte. TNS–PDADMAC–SOD shows excellent superoxide radical anion scavenging activity and is a promising candidate for applications in which suspensions with antioxidant activity are required in manufacturing processes.